Uranium concentrations in stream waters and sediments from selected sites in the eastern Seward Peninsula, Koyukuk, and Charley River areas, and across South-Central Alaska - Sharp, R.R. Jr.; Hill, D.E. (Los Alamos Scientific Laboratory, 1978)
During the summer of 1975, a 6-week reconnaissance was conducted in widespread areas of Alaska as part of the National Uranium Resource Evaluation (NURE) program; Water, stream sediment, and bedrock samples were taken from the eastern Seward Peninsula, from north of Koyukuk River, from the Charley River area, and from across south central Alaska. This report contains the LASL uranium determinations resulting from fluorometric analysis of the water samples and delayed-neutron counting of the stream sediment samples. Results of total uranium for 611 water and 641 sediment samples, from 691 stream locations, are presented. Overlays showing the numbered sample locations and graphically portraying the concentrations of uranium in water and stream sediment samples, at 1:250,000 scale for use with existing National Topographic Map Series (NTMS) sheets and published geologic maps, are provided as plates. The main purposes of this work are to make the uranium data available to the public in the standard computer format used in the NURE Hydrogeochemical and Stream Sediment Reconnaissance (i.e., with a DOE sample number giving the latitude and longitude of each sample location) and to provide uranium concentration overlays at the standard scale of 1:250,000 adopted by the DOE for the NURE program. It also allows a plausible explanation of differences between the uranium values for sediment as determined by acid dissolution/extraction/fluorometry and by delayed-neutron counting that were noted in the earlier report.